2015
DOI: 10.1007/s00261-015-0518-5
|View full text |Cite
|
Sign up to set email alerts
|

A structured approach to reporting rectal cancer with magnetic resonance imaging

Abstract: MRI is crucial for local staging of rectal cancer. A standardized approach to reporting of rectal MRI focused on communication of essential treatment planning and prognostic indicators ensures maximal added value to referring physicians to guide appropriate management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…To the best of our knowledge there have been no previous prospective studies on SRs of head and neck ultrasound examinations. Additionally, this has been one of the largest prospective studies on structured reporting in general [1013, 33, 34]. Our data showed that the use of SRs leads to significantly improved report quality, completeness and readability.…”
Section: Discussionmentioning
confidence: 54%
“…To the best of our knowledge there have been no previous prospective studies on SRs of head and neck ultrasound examinations. Additionally, this has been one of the largest prospective studies on structured reporting in general [1013, 33, 34]. Our data showed that the use of SRs leads to significantly improved report quality, completeness and readability.…”
Section: Discussionmentioning
confidence: 54%
“…stage, differentiation, location, margins of resection and dysplasia where applicable. Preoperative staging of the tumours has been performed with magnetic resonance imaging (MRI) of the rectum and endorectal ultrasound (EUS), which are proven to have high diagnostic accuracy when combined (21)(22)(23)(24). We have an established follow-up protocol for these patients with an intensive 5-year surveillance consisting of 6 monthly endoscopy, carcinoembryonic antigen (CEA), MRI scan and computed tomography (CT) scan for 3 years, which is altered to annual surveillance in years 4 and 5 (Table I).…”
Section: Methodsmentioning
confidence: 99%